Cachectic skeletal muscle response to a novel bout of low-frequency stimulation - Puppa, Melissa J. (American Physiological Society, 2014)
While exercise benefits have been well documented in patients with chronic diseases, the mechanistic understanding of cachectic muscle's response to contraction is essentially unknown. We previously demonstrated that treadmill exercise training attenuates the initiation of cancer cachexia and the development of metabolic syndrome symptoms (Puppa MJ, White JP, Velazquez KT, Baltgalvis KA, Sato S, Baynes JW, Carson JA. J Cachexia Sarcopenia Muscle 3: 117–137, 2012). However, cachectic muscle's metabolic signaling response to a novel, acute bout of low-frequency contraction has not been determined. The purpose of this study was to determine whether severe cancer cachexia disrupts the acute contraction-induced response to low-frequency muscle contraction [low-frequency stimulation (LoFS)]. Metabolic gene expression and signaling was examined 3 h after a novel 30-min bout of contraction (10 Hz) in cachectic Apc(Min/+) (Min) and C57BL/6 (BL-6) mice. Pyrrolidine dithiocarbamate, a STAT/NF-κB inhibitor and free radical scavenger, was administered systemically to a subset of mice to determine whether this altered the muscle contraction response. Although glucose transporter-4 mRNA was decreased by cachexia, LoFS increased muscle glucose transporter-4 mRNA in both BL-6 and Min mice. LoFS also induced muscle peroxisome proliferator-activated receptor-γ and peroxisome proliferator-activated receptor-α coactivator-1 mRNA. However, in Min mice, LoFS was not able to induce muscle proliferator-activated receptor-α coactivator-1 targets nuclear respiratory factor-1 and mitochondrial transcription factor A mRNA. LoFS induced phosphorylated-S6 in BL-6 mice, but this induction was blocked by cachexia. Administration of pyrrolidine dithiocarbamate for 24 h rescued LoFS-induced phosphorylated-S6 in cachectic muscle. LoFS increased muscle phosphorylated-AMP-activated protein kinase and p38 in BL-6 and Min mice. These data demonstrate that cachexia alters the muscle metabolic response to acute LoFS, and combination therapies in concert with muscle contraction may be beneficial for improving muscle mass and function during cachexia.